The Routledge Handbook of Language Revitalization - NFN Nazarudin (Masyarakat Linguistik Indonesia, 2021)
Title : The Routledge Handbook of Language RevitalizationEditor : Leanne Hinton, Leena Huss, Gerald RocheISBN : 978-1-315-56127-1 (e-book)Publisher : Routledge, 2018, pp. 552